In vitro and in vivo uncaging and bioluminescence imaging by using photocaged upconversion nanoparticles - Wang, Chao (2013)
Trading up: A bioimaging system that is based on caged D-luciferin/upconversion nanoparticle conjugate has been developed. The nanoparticles upconvert near-infrared light into UV light, which triggers the photorelease of D-luciferin (see scheme) and leads to enhanced fluorescence and bioluminescence signals in vitro and in vivo. The use of near-infrared light enables deep penetration into tissue in vivo with minimum cellular damage.